The Effect of Organizational Culture, Competence and Work Motivation on Employee Performance at Ministry of Transportation - Muhammad Rafi Dhia; Anata, Lutdhias (Philosophiamundi, 2024)
This research examines and assesses the influence of organisational culture, employee competence, and work motivation on employee performance. The data was gathered by distributing questionnaires to 78 employees at the Office of the Human Resource Development Center, Ministry of Transportation, Republic of Indonesia. The research employed an associative quantitative approach with primary data, and data analysis techniques included validity testing, reliability testing, classical assumption testing, coefficient of determination analysis (R Square), multiple linear regression analysis, hypothesis testing, and analysis using SPSS. The research findings suggest that organisational culture significantly enhances employee performance, particularly in showing respect for individuals. Additionally, the study shows that competence and work motivation positively impact employee performance, with competence being the most influential factor. The analysis of the coefficient of determination reveals that 54.7% of the variation in employee performance can be attributed to organisational culture, competence, and work motivation. At the same time, other unexamined variables, such as leadership and communication influence the remaining 45.3%